BIMBINGAN KARIR ISLAMI BERBASIS KECERDASAN MAJEMUK (SEBUAH PERSPEKTIF DAN APLIKATIF) - Adnan Achiruddin Saleh (KOMUNIDA : Media Komunikasi dan Dakwah, 2017)
Islamic career counseling is an accompaniment program conducted on High School Students / Equals through counseling and training process. This program intends to assist in determining career after finishing high school. This form of assistance is starting from potential mapping through the theory of multiple intelligences, making affirmations and goal setting, untilarrange self-efficacy. However, this paper contains the development of career theories and field experience of the author during running Islamic career guidance program in South Sulawesi.